Effect of the Transient Pharmacological Inhibition of Mapk3/1 Pathway on Ovulation in Mice - Siddappa, Dayananda; Beaulieu, Élaine; Gévry, Nicolas; Roux, Philippe P.; Bordignon, Vilceu; Duggavathi, Raj (PLOS ONE, 2015)
Mitogen-activated protein kinase 3/1 (Mapk3/1) pathway is critical for LH signal transduction during ovulation. However, the mechanisms remain incompletely understood. We hypothesized that Mapk pathway regulates ovulation through transcriptional regulation of ovulatory genes. To test this hypothesis we used immature mice superovulated with equine and human chorionic gonadotropins (eCG and hCG) and PD0325901, to inhibit hCG-induced Mapk3/1 activity. Mice received either the inhibitor PD0325901 (25 μg/g, i.p.) or vehicle at 2h before hCG stimulation. Administration of the inhibitor abolished Mapk3/1 phosphorylation in granulosa cells. While vehicle-treated mice ovulated normally, there were no ovulations in inhibitor-treated mice. First, we analyzed gene expression in granulosa cells at 0h, 1h and 4h post-hCG. There was expected hCG-driven increase in mRNA abundance of many ovulation-related genes including Ptgs2 in vehicle-treated granulosa cells, but not (P<0.05) in inhibitor-treated group. There was also reduced mRNA and protein abundance of the transcription factor, early growth response 1 (Egr1) in inhibitor-treated granulosa cells. We then used GRMO2 cell-line to test if Egr1 is recruited to promoter of Ptgs2 followed by chromatin immunoprecipitation with either Egr1 or control antibody. Enrichment of the promoter regions in immunoprecipitants of Egr1 antibody indicated that Egr1 binds to the Ptgs2 promoter. We then knocked down Egr1 expression in mouse primary granulosa cells using siRNA technology. Treatment with Egr1-siRNA inhibited Egr1 transcript accumulation, which was associated with reduced expression of Ptgs2 when compared to control-siRNA treated granulosa cells. These data demonstrate that transient inhibition of LH-stimulated MAPK3/1 activity abrogates ovulation in mice. We conclude that Mapk3/1 regulates ovulation, at least in part, through Egr1 and its target gene, Ptgs2 in granulosa cells of ovulating follicles in mice.